La incorporación de los saberes ancestrales en la práctica pedagógica en el Distrito Tambobamba, Provincia Cotabambas, Apurímac - Oscco Quispe, Sebastián (2022)
The main objective of the research is to explore the incorporation of the ancestral knowledge of parents into an intercultural pedagogy. This study was developed in the Tambobamba district, Cotabambas - Apurímac province. To do this, it investigates the theoretical concepts of ancestral knowledge in educational practice and how these contribute to developing an education with an intercultural, liberating and challenging approach, and that generates a horizontal link between others. To this end, different instruments were applied such as observation guide, interviews, and documentary analysis sheet. As a result, it was found that the incorporation of ancestral knowledge to the intercultural pedagogical practice applied by the teacher in the Initial Educational Institution (IEI) reveals, in a way, an absent intercultural education. There is an inefficient link between the actors, since they do not work in a linked manner. Consequently, this study proposes an education for change within the framework of Bilingual Intercultural Education (EIB) that develops intercultural pedagogy in the teaching-learning process.